2011
DOI: 10.1002/ardp.201000029
|View full text |Cite
|
Sign up to set email alerts
|

NMR QSAR Model for the Analysis of 4‐(5‐Arylamino‐1,3,4‐thiadiazol‐2‐yl)benzene‐1,3‐diols

Abstract: We have developed a NMR data quantitative structure-activity relationship NMR-QSAR model based on (1)H- and (13)C-NMR experimental spectral data of 4-(5-arylamino-1,3,4-thiadiazol-2-yl)benzene-1,3-diols. Compounds show in-vitro antiproliferative activity against some human cancer cell lines. Two-parameter equations obtained by the multiple linear regression procedure showed that chemical shifts of the protons of hydroxyl groups and carbon atoms of the 1,3,4-thiadiazole ring are the decisive descriptors of inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…To extend our studies in this area, a set of new heterocyclic analogs with 2,4dihydroxyphenyl functionality were designed and obtained. Following from previous studies, this group of compounds exhibits strong antifungal and antiproliferative activity [34][35][36][37][38][39]. This paper presents the in vitro antifungal potency of compounds against the panel phytopathogenic fungi and Candida strains as well as cytotoxic potency against human cancer cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…To extend our studies in this area, a set of new heterocyclic analogs with 2,4dihydroxyphenyl functionality were designed and obtained. Following from previous studies, this group of compounds exhibits strong antifungal and antiproliferative activity [34][35][36][37][38][39]. This paper presents the in vitro antifungal potency of compounds against the panel phytopathogenic fungi and Candida strains as well as cytotoxic potency against human cancer cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…Many synthetic methods were reported in the literature for the synthesis of 1,3,4‐thiadiazole derivatives, for example, sulfuration of the corresponding 1,4‐dicarbonyl or acyl precursors using P 2 S 5 and Lawesson's reagent and also prepared from (i) carboxylic acids using propylphosphonic anhydride in one pot, (ii) from acid hydrazides under microwave irradiation in a single step , and (iii) N , N ‐diacylhydrazines in presence of P 2 S 5 and Lawesson's reagent and various other methods also reported .…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative structure–activity relationship (QSAR) is an important and common research tool in the modern bioactive molecule design . It was found that the NMR chemical shift is a good descriptor and plays a significant role in the QSAR studies of alcohols, benzene sulfonamides, and 1,3,4‐thiadiazoles …”
Section: Introductionmentioning
confidence: 99%